The Use of Brown Rice Flour as a Substitute for Wheat Flour in the Production of Madeleine Cake - Dewi Fitriani; Ita Karnita; Annisa Metrasari (Universitas Pendidikan Indonesia, 2023)
Madeleine cake or commonly referred to as petite madeleine is a small French version of the butter cake. This madeleine cake has a unique shape characteristic that is in the form of a clamshell and then has a 'bump' or part that expands on the back side of the cake. (Sam, 2020). These little cakes have been loved by kings and peasants since the 17th century, and were ingrained in French hearts and culture by the French philosopher Proust in the early 1920s. (Ledsom, 2018). Whole grain rice is rice that contains three edible components, namely the bran, germ, and endosperm. Meanwhile, refined rice is rice that is polished to remove parts of the bran and germ so that only starchy white endosperm remains, hence the name “white” rice. (Harvard T.H. Chan, 2022). Researchers want to spread Madeleine Cake to the people of Indonesia with a unique and healthy variant, namely the replacement of flour raw materials with the use of local ingredients, namely brown rice flour. With the hope that the product can be healthier, has a more unique aroma, taste and texture to be enjoyed by various group of people.